Czy milczenie zawsze jest złotem? Percepcja ciszy i milczenia na zajęciach z praktycznej znajomości języka angielskiego - Wiśniewska, Danuta (Neofilolog, 2019)
Formal foreign language teaching involves verbal and non-verbal interactions among the participants of language classes. The nature of these interactions may play a decisive role in the success or failure in language learning. The research described in this paper attempted to gain insight into students' perceptions of silence occurring during classroom language learning, to identify its causes and effects, and to appraise its potential value for learners.